Role of the cAMP signaling pathway in the dissemination and development on pepper fruit anthracnose disease caused by Colletotrichum scovillei - Fu, Teng; Park, Hyun-Hoo; Kim, Kyoung Su (Frontiers in Cellular and Infection Microbiology, 2022)
The ascomycete fungus Colletotrichum scovillei causes severe anthracnose disease on the fruit of sweet pepper and chili pepper (Capsicum annuum L.) worldwide. Understanding the biology of C. scovillei would improve the management of fruit anthracnose diseases. The cyclic adenosine monophosphate (cAMP) signaling pathway regulates diverse cellular and physiological processes in several foliar fungal pathogens. We investigated the roles of the cAMP signaling pathway in C. scovillei using pharmaceutical and genetic approaches. Exogenous cAMP was found to increase conidiation, appressorium formation, and anthracnose disease development in C. scovillei. CsAc1, CsCap1, and CsPdeH, which regulate the intracellular cAMP level, were deleted by homology-dependent gene replacement. Expectedly, the intracellular cAMP level was significantly decreased in ΔCsac1 and ΔCscap1 but increased in ΔCspdeh. All three deletion mutants exhibited serious defects in multiple fungal developments and pathogenicity, suggesting regulation of the intracellular cAMP level is important for C. scovillei. Notably, exogenous cAMP recovered the defect of ΔCsac1 in appressorium development, but not penetration, which was further recovered by adding CaCl2. This result suggests that CsAc1 is associated with both the cAMP and Ca2+ signaling pathways in C. scovillei. ΔCscap1 produced morphologically abnormal conidia with reduced tolerance to thermal stress. ΔCspdeh was completely defective in conidiation in C. scovillei, unlike other foliar pathogens. Taken together, these results demonstrate the importance of cAMP signaling in anthracnose disease caused by C. scovillei.